The influence of actor Choi Siwon as the brand ambassador of Mie Sedaap Korean Spicy Chicken on purchasing intention of university students (a study on psychology students at Makassar State University - Ediman, Haerunnisa; Tajibu, Kamaluddin; Mannan, Audah (Jurnal Mercusuar, 2020)
The role of advertising in influencing consumer buying interest is an interesting phenomenon, especially if the advertisement is portrayed by K-POP members whose fans are quite popular among Indonesian teenagers and college students. Therefore, Choi Siwon (one of the K-POP members) as a brand ambassador for Mie Sedaap receives more attention, especially since this study takes psychology students as the research subjects. Using a descriptive quantitative research method, this study found that interest in attractiveness showed a presentation of 96% of 88 respondents, 89% showed a level of confidence in the integrity of the brand ambassador, and 93% of respondents answered that Choi Siwon was suitable to advertise the product. Based on the buying interest variable, 68% with 63 respondents within a month showed that they were interested in buying the product, with 46% of 42 respondents answering that they consumed Mie Sedaap Korean Spicy Chicken as a substitute for a side dish. In addition, 78 respondents with a percentage of 85% answered that they would recommend the product for consumption. Meanwhile, the lowest frequency is found in the promotion aspect, with a frequency of 67 respondents with a percentage of 73% answering that they have ever promoted the product.